Building the cooling roads with high thermal conductivity pavements to relieve urban heat island effect. (5th September 2022) - Pan, Fei; Pei, Jianzhong; Zhang, Gewei; Wen, Yong; Zhang, Jiupeng; Li, Rui
Highlights: Quartzite instead of limestone contributed to the thermal inertia of pavement. An environmental chamber was made to simulate the daily heating and cooling process. HTCP reduces the maximum road temperature but worsens the UHI at night. Abstract: This study aims to propose a new highly thermally conductive pavement (HTCP) structure and evaluate the cooling effect of the structural layers and near-surface air. The HTCP consisted of coarse quartzite aggregates with high thermal conductivity instead of limestone. The HTCP and conventional asphalt pavement layers were placed in the environmental chamber. The incandescent lamp was used to simulate solar radiation to analyze the air temperature changes of the structural layers and near-surface air. The test results show that quartzite improves the thermal inertia of asphalt pavement layers. And the HTCP effectively transfers the heat accumulated in the upper layer and reduces the daily temperature of structure layers and near-surface air. However, HTCP releases more sensible heat at night, negatively impacting the urban heat island effect. This research contributes to the improvement of HTCP from an aggregate perspective and provides new ideas for mitigating the UHI effect.